Pengaruh Penerapan Kurikulum 2013 Terhadap Hasil Belajar PAI di Kelas VIII - Wardani, Dian Kusuma; Fitriah, Arinda Nurul; Devitasari, Afada (Universitas KH. A. Wahab Hasbullah, 2024)
This study aimed to determine the effect of implementing the 2013 curriculum on learning outcomes of Islamic religious (PAI) classes VIII E and F at SMPN 2 Tembelang. The research method used is a quantitative research method, where the research instrument used is in the form of a questionnaire and student learning outcomes obtained from student report cards with an average score of 84,9, with the lowest score being 73 and the highest score being 94. Based on the normality test of the two classes, it has a normal distribution with a significance value of 0,200 > 0,05. Based on hypothesis testing using the t-test, a significance result of 0,000 > 0,05 is obtained so that H0 is rejected and H1 is accepted. This means that it can be concluded that the 2013 curriculum variable (X) affects the learning outcomes of Islamic religious education (Y) subject at SMPN 2 Tembelang.